PENGARUH FINANCIAL DISTRESS, KEPEMILIKAN TERKONSENTRASI, GOOD CORPORATE GOVERNANCE DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK - Prasetyo, Bayu Eko; Yusuf, Nur’Aini (Publika Citra Media, 2025)
This study aims to analyze the influence of financial distress, concentrated ownership, good corporate governance, and capital intensity on taxaggressiveness. This research was conducted by analyzing the finansial statements of companies in the energy sector listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The sample used in this study consisted of 13 energy sector companies listed on the Indonesia Stock Exchange during the period from 2019 to 2023, using the purposive sampling technique. The data used in this research are secondary data in the form of financial statements from each company that has been sampled for the study. The variables used in this study are financial distress, concentrated ownership, good corporate governance, capital intensity as the independent variable with tax aggressiveness as the dependent variable. The panel data regression method is used as the research methodology in this study. Analysis of research results using the EViews 12 Student Version Lite software. The research results show that the best model is the Common Effect Model. (CEM). The results of this study indicate that financial distress partially does not affect tax aggressiveness, concentrated ownership partially does not affect tax aggressiveness, good corporate governance proxied with independent commissioners partially does not affect tax aggressiveness, capital intensity partially affects tax aggressiveness, and simultaneously, financial distress, concentrated ownership, good corporate governance, and capital intensity affect tax aggressiveness.